A STUDY ON THE PISCIFAUNA OF THE IDUKKI RESERVOIR AND CATCHMENT AREA - GOPINATH, P; JAYAKRISHNAN, T N (Fishery Technology, 2017)
From the area under report 17 species, 15 endemic and 2 exotic, of freshwater fish have been identified. Of these, 8 species are commonly found in the catches and are of fishery significance. The fact that small fish species which have no fishery importance also support life in other trophic levels of this ecosystem is well exemplified by the interaction of the birds and mammals with these species. A scientific management and monitoring of the reservoir waters as well as the remaining segments of forests are recommended to salvage the wild life and vegetation from a possible rapid deterioration within years